Proceso de atención nutricional en paciente femenino de 57 años de edad con tuberculosis. - Caballero Alcantaro, Johanna Alexandra (2023)
The present clinical case consists in the nutritional evaluation of a patient who arrives to the emergency area with her relatives due to persistent cough accompanied by respiratory distress, hemoptoic stupus, general malaise, weight loss and unquantified thermal rise, it is decided hospital admission; Subsequently, pertinent complementary biochemical tests are requested where tuberculosis is diagnosed; The doctor requests nutritional consultation for intervention and her nutritional status is evaluated through anthropometric, biochemical, clinical/physical, and dietary indicators. Once the patient's medical history and its assessments have been obtained through previously mentioned indicators, malnutrition is observed according to body composition evidenced by a deficient intake of food groups and biochemical tests. The nutritional treatment began with a slow feedback to avoid complications that could affect her health, a gradual change of kcal divided into 6 meal times was made until achieving an optimal food intake established according to her total energy expenditure.